MORPHO-BIOCHEMICAL FEATURES OF THE RAT’s PANCREAS UNDER CONDITIONS OF PANCREATIC DUCT OCCLUSION - Makarchuk, V.A.; Ushakova, G.A.; Babiy, A.M.; Shevchenko, B.F.; Oshmyanskaya, N.Y. (World of Medicine and Biology, 2014)
We prepared 2 experimental groups: rats with short-term (group 1) and prolonged (group 2) occlusion of the pancreatic duct. Abnormal deposition of collagen with subsequent development of fibrosis in pancreas occurs in group 2, as confirmed by morphometry (ratio of fibrous tissue to the total biopsy area) and biochemical analysis (determination of fibrosis markers – hyaluronic acid, protein-bonded hydroxyproline and free hydroxyproline). Furthermore, present study defines numerical intervals of biochemical coefficients “coefficient protein-bonded hydroxyproline / coefficient free hydroxyproline”, which characteristically present in acute and chronic stages pancreatitis after prolonged pancreatic duct occlusion: inflammatory-necrotic stage of acute pancreatitis – 1,09–1,43; atrophic-profibrotic stage of acute pancreatitis – 1.44–1.78; fibrotic stage of chronic pancreatitis – 1.79 and more.
Keywords: pancreatitis; pancreas; occlusion; fibrosis